Numerical and experimental investigations into the response of STF-treated fabric composites undergoing ballistic impact. (October 2017) - Hasanzadeh, Mahdi; Mottaghitalab, Vahid; Rezaei, Mohammad; Babaei, Hashem
Abstract: This paper deals with the experimental and numerical investigation of the impact resistance properties of woven high modulus polypropylene (HMPP) fabrics impregnated with shear-thickening fluids (STFs) composed of fumed silica nanoparticles suspended in polyethylene glycol (PEG). The impact of ogival tip projectile on four-layered fabrics was simulated using LS-DYNA ® . One important issue addresses the effect of STF impregnation on improving the ballistic properties of woven fabrics. The effect of STF impregnation on fabric are taken into account as the friction between the yarns and their crossovers and the friction between projectile and fabric during impact. Comparing the depth of indentation of samples with the corresponding experimental data reveals acceptable agreement between the results of the computational analysis and experiments. Both the numerical and experimental investigations on the impact resistance of neat and STF-treated HMPP fabric confirmed the contribution of frictional properties induced by STF impregnation in restriction of the yarns within the fabric. Highlights: Ballistic performance of STF-treated fabric composites are studied. New model developed to predict the behavior of HMPP/STF fabric under ballistic impact. HMPP/STF fabric suggest better penetration resistance than the neat fabric.